2015
DOI: 10.4314/njt.v35i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polythene Fibres on Selected Properties of Sandcrete Blocks

Abstract: The aim of this study is to explore the possibility of using polythene fibres to increase the strength of sandcrete The aim of this study is to explore the possibility of using polythene fibres to increase the strength of sandcrete The aim of this study is to explore the possibility of using polythene fibres to increase the strength of sandcrete The aim of this study is to explore the possibility of using polythene fibres to increase the strength of sandcrete blocks without increasing the weight and cost of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…However the control sample 0% FCC and the 10% FCC have a better water absorption property of 85kg/m 3 while the water absorption rate for the 20% FCC and 30% FCC were 120kg/m 3 and 90kg/m 3 respectively. This means that 10% FCC can be use in water logged areas and get same result as when using the normal sandcrete blocks without any addition of shredded polythene bags waste as reported by [10,12]…”
Section: Compressive Strengthsupporting
confidence: 62%
See 1 more Smart Citation
“…However the control sample 0% FCC and the 10% FCC have a better water absorption property of 85kg/m 3 while the water absorption rate for the 20% FCC and 30% FCC were 120kg/m 3 and 90kg/m 3 respectively. This means that 10% FCC can be use in water logged areas and get same result as when using the normal sandcrete blocks without any addition of shredded polythene bags waste as reported by [10,12]…”
Section: Compressive Strengthsupporting
confidence: 62%
“…Also, the process of fly ash brick manufacturing results in lesser pollution. A studies by [10,11,12] on the possibility of using polythene fibres to increase the strength of sandcrete blocks without increasing the weight and cost of production with the addition of 0.25%, 0.5% and 0.75% shredded polythene bags, revealed that the addition of polythene fibre to sandcrete blocks has very little effect on the compressive strength, although at 0.5% fibre content, the tensile strength increased. They study further reported that the compressive strength of the heated blocks is higher than the non -heated blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Hence there is a need for assessing the knowledge on harmful effect of use of polythene & plastic materials on health & environment among school age children residing in rural community areas of Indore city. [12][13][14][15]…”
Section: Need Of the Studymentioning
confidence: 99%
“…Incorporation of short discrete steel fibres in a relatively hollow sandcrete blocks matrix, might gives the hollow sandcrete blocks materials a maximum ductility to overcome its low tensile strength properties. Similarly [14] reported that addition of polythene fibres to sandcrete blocks improves the tensile strength and limit the propagation of cracks, although it has little effect on the compressive strength. Recycled tyre steel fibres are obtained from recycling of scrap tyres [15].…”
Section: Introductionmentioning
confidence: 99%